Macrostomia Surgery Using Small Z-plasty for Construction of the Corner of the Mouth - Yuka Hirota, MD, PhD; Aya Yoshikawa, MD; Hiromi Kino, MD, PhD; Koichi Ueda, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Macrostomia is a type of transverse facial cleft (termed number 7 in the Tessier classification) and a disorder in which there is a cleft on 1 or both sides of the corner of the mouth. The Kaplan technique is used for the treatment of macrostomia and is characterized by forming the corners of the mouth with a single continuous flap of vermilion. In this technique, there are no suture lines at the commissure; thus, it does not cause contracture at the corners of the mouth. We performed a small Z-plasty on the outer edge of the flap at the corner of the mouth, constructed using the Kaplan technique to emphasize the upper and lower lip borders by referring to the Onizuka opinion regarding the shape of the corners of the normal mouth. The lengthening effect of Z-plasty is caused by lateral skin mobility, which results in distortion of the skin plane. The flaps are moved, and the sutured central line is depressed into a web-like structure. This effect was utilized in our technique, and this depression was matched to the corner of the mouth. By effectively using Z-plasty, we were able to clarify the boundary between the upper and lower lips. Our small Z-plasty technique for macrostomia surgery resulted in a favorable, natural shape of the mouth corner.